MATHEMATICAL MODEL OF THE PHYSICAL PROCESS OF HACKING TECHNICAL PROTECTION OF INFORMATION - Zhurilenko, Boris; Nikolaev, Kirill; Ryabova, Lyubov (Ukrainian Information Security Research Journal, 2022)
This paper presents a mathematical model of the physical process of breaking technical information security (TIS). The mathematical model is based on the works of B. Zhurylenko, which use: the funding invested in protection, the coefficient of protection efficiency and the direction of hacking. The mathematical model was built taking into account the Poisson distribution used in the theory of queuing. The Poisson distribution allows us to take into account the probability of a particular attempt and its time of breaking information security. Studies have shown that, in the absence of funding for protection, the probability of breaking will be determined only by the Poisson distribution and the probability of breaking the applied protection. In the presence of funding for information protection, there are differences between the distributions of the probability and the maximum probability of hacking, with the distribution of the probability of hacking having a maximum value at a certain point, and the distribution of the maximum probabilities of hacking is exponential. In addition, these distributions have a highly directional character with the maximum probability value in the direction of the break line. The values of probabilities decrease with distance from the line of the burglary direction, increasing the burglary coordinates and time. If the real direction of hacking differs from the projected one, the probability of the maximum value of a possible hacking of the TIS changes. It is shown that in this case the probability of possible hacking decreases, since the area of intersecting surfaces of probabilities of real and possible hacking decreases. An expression has been introduced into the mathematical model of the physical process of breaking TIS, which determines the probability of breaking the alleged protection. Thus, as a result of the work performed, we obtained a mathematical model of the physical process of hacking TIS, which is described by the following parameters: the funding invested in the protection, the effectiveness of the funding invested in the protection, the direction of the hacking attempts and their intensity, the probability of a particular hacking attempt and the probability of hacking the alleged TIS.